Correspondence between alternate measures of maladaptive exercise, and their associations with disordered eating symptomatology - Lease, Haidee J. (Akadémiai Kiadó, 2013)
Aims: The study sought to contribute to the measurement of maladaptive exercise by examining the psychometric properties of a variety of instruments and classification algorithms. The primary aim was to identify the items or scales necessary and sufficient to quantify the construct. A secondary aim was to comment on the construct validity of these measures by examining their relationships with disordered eating symptomatology. Methods: Questionnaire booklets comprising the Exercise Dependence Scale, the Obligatory Exercise Questionnaire, the Frequency, Intensity, Time Index, and the Eating Attitudes Test were distributed to women attending health and fitness centres. Self-reported age, height, current and desired weight, and length of time as a regular exerciser were also sought. Data were obtained from 302 regular exercisers. Results: While there were statistically significant associations among the measures, no two operationalised maladaptive exercise in the same manner. The Frequency-Intensity-Time Index (FIT) was found to be particularly poor. While variation in the size of relationships between maladaptive exercise and disordered eating was noted, all measures were strongly correlated with the exception of FIT, which demonstrated a modest correlation. Conclusions: Different conceptualisations of maladaptive exercise have led to alternative operational definitions, resulting in its classification being instrument dependent. Further exploration using samples with differing characteristics (e.g., high/low probability of dependence) may allow more specific recommendations to be made about the optimal measurement of maladaptive exercise. Further, the question of whether maladaptive exercise is more likely a cause or consequence of eating disorders remains.